TÉCNICAS E INDICADORES PARA LA EVALUACIÓN DE PORTALES EDUCATIVOS EN INTERNET - Bedriñana Ascarza, Aquiles (2005)
It given some preliminary ideas of differences between the web pages and the educational entries. Every entry is a web page but not every web is an entry. This article presents a slip for cataloguing and educational entries whose author is Pere Marqués, UAB, 2001. Also he is necessary to do an appreciation criticizes if the present web page of the Greater National University of San Marcus has the category of an educational entry with these bases will be designed the educational entry of the Faculty of Administrative Sciences.